Sámi shop on Kirkegata in Tromsø, Norway ... - Campbell, Sandy (University of Alberta Library, 2024)
Tromsø, Norway receives many cruise ships, brining tourists to the city. Near the harbour there are many shops catering to tourists, including gift and souvenir shops. The Sámi Shop specializes in Sámi handicrafts and products, including products made from reindeer (hides, antler knife handles), silver jewelry, knitted items and objects using traditional Sámi fabric patterns and images of reindeer. Sámi are Indigenous people of Sámpi, a region that includes northern parts of Norway, Sweden, Finland and northwest Russia. ...